Desenho e linha: modos de Pensamento e Expressão (Revista Apotheke, 2019)
This paper addresses some considerations about the content approached in the second chapter of my thesis, which extends to the questions of the line in its generais scope and in the specific one of the drawing. The study involves the theme of drawing as being a direct means of expression and the presence of the line acting in the ordering of our abstract thinking. It is questioned to what extent the proximity with the drawing in the day to day, by its character of annotation or orientation, could activate its practice as a means of creation in the arts. I conclude by presenting three contemporary artists who work on the problematic of the line in the expanded field of drawing.
Keywords: line; drawing; extension of trought; expression